An Assement of Cane Potential of Baratang Island In South Andaman Forest Division - Sharma, S. K.; Bhatt, P. M. (Indian Forester, 1982)
The cane resources of the country are fast depleting due to heavy demand and Andaman & Nlcobar Islands are considered to be the last basting for availability of canes to meet the demand locally as well as on the main land. In order to find out the possibility of meeting the cane requirement of Sports Goods Export Promotion Council, an assessment of cane potential in Baratang Island was made adopting the random sampling method. An area of 3223 hectares was divided into 123 primary blocks of which 32 primary blocks Were randomly selected. 3 secondary blocks of one hectare each were demarcated in each primary block. To avoid labour and wastage, secondary blocks were further divided into 4 equal parts to take one of the 0.25 hectare area for data collection. Only 4 species of canes Out of 7 species were considered as the other cane species are seldom found in Baratang Island. 3 commercial species viz., Calomus andamanicus, Calomus pseudorivalis and Korthalsia lactniosa and Calamus longisetus though not commercial, but occurs Very frequently in Baratang Island were considered. It was revealed that the potential of canes in Baratang Island with regard to standard error.